2010
DOI: 10.3390/s100908398
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Electrochemical Sensor for Probing Doxepin Created on a Glassy Carbon Electrode Modified with Poly(4-Amino- benzoic Acid)/Multi-Walled Carbon Nanotubes Composite Film

Abstract: A novel electrochemical sensor for sensitive detection of doxepin was prepared, which was based on a glassy carbon electrode modified with poly(4-aminobenzoic acid)/multi-walled carbon nanotubes composite film [poly(4-ABA)/MWNTs/GCE]. The sensor was characterized by scanning electron microscopy and electrochemical methods. It was observed that poly(4-ABA)/MWNTs/GCE showed excellent preconcentration function and electrocatalytic activities towards doxepin. Under the selected conditions, the anodic peak current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…In supporting electrolytes pH values above 5.0, ROP gave two separate oxidation steps. Taking into account the break point of Ep 2 vs. pH plot for Ox 2 and anodic voltammetric behaviour of some drugs which have tertiary amine group as only electroactive site on the molecule like doxepin, 25 the second oxidation step (Ox 2 ) appeared in neutral and alkaline conditions could be located on the aliphatic nitrogen. After deprotonation, ROP lost an electron to form a cation radical which in subsequent step formed a quaternary Schiff base by losing a proton and an electron.…”
Section: Electrochemical Oxidation Of Ropmentioning
confidence: 99%
“…In supporting electrolytes pH values above 5.0, ROP gave two separate oxidation steps. Taking into account the break point of Ep 2 vs. pH plot for Ox 2 and anodic voltammetric behaviour of some drugs which have tertiary amine group as only electroactive site on the molecule like doxepin, 25 the second oxidation step (Ox 2 ) appeared in neutral and alkaline conditions could be located on the aliphatic nitrogen. After deprotonation, ROP lost an electron to form a cation radical which in subsequent step formed a quaternary Schiff base by losing a proton and an electron.…”
Section: Electrochemical Oxidation Of Ropmentioning
confidence: 99%
“…CV was performed from −1.4 to + 2.4V for ten cycles with a scan rate of 100 mV s −1 . Before being used, the modified electrode was again electropolymerized with CV from +0.3 to +1.2 V in a 0.1 M phosphate buffer solution of pH 7 until it was a stable cyclic voltammogram (Xu et al, 2010).…”
Section: Fabrication Of a Working Electrodementioning
confidence: 99%
“…Poly(4-amino-benzoic acid) was used instead of Nafion to measure doxepin [256], polycysteic acid for sinomenine [257] and chitosan matrices either to measure acetaminophen and mefenamic acid simultaneously [258] or dipyrone [259]; in this latter case, the CNTs are covalently bound to the matrix [259]. Single-walled carbon nanotube (SWCNT)-and MWCNT-modified carbon ceramic electrodes were compared for nanomolar detection of acetaminophen [260], it being found that the current enhancement and electrocatalytic effects were better using SWCNT.…”
Section: Screen-printed Electrodesmentioning
confidence: 99%